The influence of host country national support on expatriate success in Malaysia - Chan, Hak Liong; Zawawi, Dahlia; Ng, Siew Imm (Faculty of Economics and Administration, University of Malaya, 2015)
This study examines the effects of host country national (HCN) support on expatriate adjustment and withdrawal intentions, and in turn expatriate performance. This study aims to improve the problems of cross-cultural adjustment concerning general living, work and interaction faced by expatriates in shared services and outsourcing (SSO) industry in Malaysia. In order to provide a broader view of expatriate success, it is critical to study cross-cultural adjustment, job performance and withdrawal intentions concurrently in this research. Stakeholders are groups of entities or individuals that are important to expatriates where HCNs are parts of them. Therefore, this study intends to explore the support HCNs in influencing expatriate success, particularly withdrawal intentions as the ultimate success criterion. In addition, this research is corroborated by job demands and resources (JD-R) model.